Analisis Struktur dan Aspek Kebahasaan Teks Berita Korupsi pada Media Tempo.Co sebagai Rekomendasi Modul Pembelajaran Teks Berita Kelas VII: Analysis of Structure and Linguistic Aspects of Corruption News Texts in Tempo.Co Media as a Recommended Module for Class VII News Learning - Anisa Salsabila; Sinta Rosalina; Hendra Setiawan (Universitas Tidar, 2025)
This study is motivated by the importance of understanding text structure and linguistic aspects in news texts as a foundation for developing students’ critical literacy skills. The objectives of this research are (1) to describe the forms and functions of structure and linguistic aspects found in corruption news texts published on the online media Tempo.co, and (2) to utilize the research findings as recommendations for developing a news text learning module for seventh-grade Indonesian language classes. This research employed a qualitative approach with a descriptive design. The analysis of news text structure refers to Musman and Mulyadi (2021), while the analysis of linguistic aspects is based on the framework proposed by Kurniawan and Kosasih (2018). The data consist of corruption news articles from the Peristiwa section of Tempo.co, focusing on text structures such as titles, place, and date of events, leads, and bodies of news; as well as linguistic aspects including the use of standard language, direct sentences, the conjunction that, mental verbs, time and place adverbials, and temporal conjunctions. The results show that the structure of the news texts on Tempo.co is complete and systematically organized, applying an inverted pyramid model that places the most essential information at the beginning. The linguistic aspects are consistently aligned with the characteristics of formal news language, demonstrating factuality, accuracy, and objectivity. Based on these findings, the researcher proposes a learning module for teaching news texts in seventh-grade Indonesian language classes. This module is expected to enhance students’ ability to understand text structures and linguistic features, as well as foster critical awareness of media discourse.